Cross-Cultural Validity of the Grief Impairment Scale (GIS): Evidence From Four Latin American Countries - Caycho-Rodríguez, Tomás (2024)
The Grief Impairment Scale (GIS) is used to measure functional impairment due to grief following the death of a loved one. However, there is no information on its cross-cultural utility. Thus, this study assessed the measurement invariance of the GIS using a large sample of bereaved adults (N = 2060) from Peru, El Salvador, Ecuador, and Colombia. Specifically, we employed two measurement invariance techniques: multi-group confirmatory factor analysis (MG-CFA) and the alignment optimization method. The results indicated that the GIS demonstrated configural and metric invariance, but not scalar invariance through MG-CFA. The alignment optimization method indicated the presence of an approximate invariance. Therefore, the results suggest that the GIS measures grief-related impairment similarly across the four Latin American countries. Among the countries examined, Peru reported the highest average score on the GIS and had the highest percentage of cases at risk for clinically relevant functional impairment due to grief (6.2%). These findings support the cross-cultural validity of the GIS and lay the foundation for future comparisons.